A Distribution Network Reconfiguration Algorithm Based on Hopfield Neural Network - Weixin Gao; Nan Tang; Xiangyang Mu (2008 Fourth International Conference on Natural Computation, 2008)
On the base of Hopfield neural network, the minimum of feeder looses is treated as the target function. Because the distribution network is radical, we put forward a method for deciding each node's in-degree by using Hopfield neural network. According to each node's in-degree, it can be easily determined whether the line will be used or not. So the state of switch and the scheme of reconfiguration can be decided correspondingly. The energy function of Hopfield neural network is given in this paper. The problems of satisfying the restriction of radial supplying and minimizing the feeder power looses are considered in the energy function simultaneously. The energy function even takes the problem that some lines may have no switches into consideration. By calculating an IEEE distribution network with three power sources, it can be found that the calculated result of Hopfield neural network is somewhat similar to the result obtained by the more complex genetic algorithm. Since the former is to calculate a group of differential function, so the calculation time needed is comparatively less.